2014
DOI: 10.1016/j.jad.2014.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Cingulum bundle white matter lesions influence antidepressant response in late-life depression: A pilot study

Abstract: Background Late-life depression is associated with white matter hyperintense lesions (WMLs) occurring in specific fiber tracts. In this study, we sought to determine if greater WML severity in the cingulum bundle or uncinate fasciculus was associated with poor short-term antidepressant response. Methods Eleven depressed elders completed a baseline cranial 3T MRI and received antidepressant treatment following a medication algorithm. MRIs were analyzed to measure the fraction of each fiber tract’s volume occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…The two highest-powered studies thus far have supported a predictive value of the fractional anisotropy of the left cingulum bundle for ADM treatment remission/non-remission (Korgaonkar et al, 2015;Korgaonkar et al, 2014b). Indirectly supportive of this finding, Taylor et al (2014) showed, in a small population of 11 elderly MDD patients, a relationship between a higher density of white matter lesions in the left cingulum bundle and worse treatment response (Taylor et al, 2014).…”
Section: Diffusion Biomarkersmentioning
confidence: 85%
“…The two highest-powered studies thus far have supported a predictive value of the fractional anisotropy of the left cingulum bundle for ADM treatment remission/non-remission (Korgaonkar et al, 2015;Korgaonkar et al, 2014b). Indirectly supportive of this finding, Taylor et al (2014) showed, in a small population of 11 elderly MDD patients, a relationship between a higher density of white matter lesions in the left cingulum bundle and worse treatment response (Taylor et al, 2014).…”
Section: Diffusion Biomarkersmentioning
confidence: 85%
“…Therefore, one possible interpretation of the association between WMH accumulation and non-remission is that the former represents further degradation of these neural pathways, which are critical to patient recovery. This hypothesis arises from a number of previous studies, which demonstrate that WMHs and microstructural abnormalities in specific frontostriatal circuit structures are associated with treatment outcomes in LLD (Alexopoulos et al, 2002(Alexopoulos et al, , 2008(Alexopoulos et al, , 2010Taylor et al, 2014). It is also a distinct possibility that this effect is bidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one of the most salient models of depression in older adults is the vascular depression hypothesis, which suggests that cerebrovascular ischemic damage promotes depressive symptoms Butters et al, 2008). The relationship between WMHs and the vascular depression hypothesis is further strengthened by studies demonstrating that WMHs are associated with treatment outcomes (Aizenstein et al, 2011;Firbank et al, 2007;Heiden et al, 2005;Taylor et al, 2014). However, as several other studies have failed to find the association between WMHs and depression, the vascular depression hypothesis is not universally accepted (Aizenstein et al, 2011;Dotson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…20 Damage to such circuits may predispose individuals to depression and diminish the ability of antidepressants to modify brain function and connectivity, resulting in poorer clinical response. 21 Thus clinically relevant depressive symptoms in context of mild cognitive symptoms may be an early marker of brain pathology. Second, a “depression neurotoxicity” hypothesis proposes that repeated depressive episodes contribute to pathological brain aging and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%